Interoceptive sensibility and alcohol craving in Polish prisoners: the role of alexithymia and emotional dysregulation - Ścigała, Dawid Konrad; Fabris, Matteo Angelo; Zdankiewicz-Ścigała, Elżbieta; Kuc, Krystian; Longobardi, Claudio (Frontiers in Psychology, 2024)
Introduction Alcohol craving, characterized by a strong desire or compulsion to consume alcohol, is a prominent symptom of substance dependence syndrome. Research indicates that alcohol craving is a significant factor leading to the termination of abstinence. The mechanisms underlying the activation of alcohol craving remain not fully understood. The urge to reach for alcohol may be stimulated by emotions, memories, thoughts, or bodily sensations, as well as external factors. It has been postulated that individuals with high levels of interoceptive sensibility tend to exhibit a high degree of alexithymia and emotion dysregulation in the context of alcohol craving. Deficits in identifying and verbalizing emotions, along with an operational thinking style, facilitate alcohol consumption by impeding accurate insight into one’s mental state, thereby hindering the comprehension of bodily states, emotions, and the regulation of self. Method This study involved 160 inmates incarcerated in a prison in Poland, awaiting participation in therapy for individuals with substance dependence following psychiatric diagnosis. Four questionnaires were used in the study: multidimensional Assessment of Interoceptive Sensibility (MAIA) for interoceptive sensibility, Toronto Alexithymia Scale (TAS-20) for alexithymia, Difficulties in Emotion Regulation Scale (DERS) for emotional dysregulation, and the Penn Alcohol Craving Scale (PACS) for alcohol craving assessment. Results The results of the study are as follows: the study findings indicated that alexithymia and emotional dysregulation significantly mediates the relationship between interoceptive sensibility and alcohol craving. The indirect effect for both factors was found to be significant, similar to the indirect effect observed for alexithymia as an mediator. However, in the case of emotional dysregulation, no significant indirect effect was observed. Conclusion Our study provides insights into the potential contribution of interoceptive sensibility to the heightened risk of alcohol dependence. Specifically, impaired interoceptive sensibility may be associated with the development of alexithymia and emotional dysregulation, potentially rendering individuals more susceptible to alcohol craving. Interoceptive sensibility could serve as a prerequisite for the cultivation of positive emotional processing skills.